QUALIDADE DE VIDA NO TRABALHO: COM A PALAVRA OS FUNCIONÁRIOS PÚBLICOS - Garcia, Edilene de Oliveira Pereira (2007)
The subject of this research is the Quality of Working Life (QWL) of public officers of the Health Department of Barra Mansa local government. It is a case study of quanti-qualitative, exploratory and descriptive nature that has as objectives to understand what QWL is for these public officers, to verify what are the perceptions they have concerning their own QWL and, to understand if in the public sphere it is possible to construct new senses for QWL which approach it to a commitment with collectiveness and life. Walton s QWL model, the analysis of instruments used in eleven other researches carried through several Brazilian education institutions and the collection of seven depositions of public officers, concerning their professional histories and general impressions on QWL have guided the elaboration of the instrument used in this research. 205 valid questionnaires have been collected, which were considered enough for the use of the factorial analysis as statistical method by software SPSS. Moreover, two depositions were collected, through opened interviews, which added to the seven already gotten, were used in the qualitative analysis of the results. The main joined results point that QWL of the searched public officers is reasonable or good, and that they associate it to a series of objective and subjective aspects of life at work. Many of them are within Walton s model, however some that had emerged the model does not enclose. It is exactly inside this gap that seems to be possible to construct new senses for QWL that approach it to a commitment with collectiveness and life, in a different logic of that individualist and instrumentalist that mark its origin in the private sector. From this point on, it is possible to think in participative public policies.